2014
DOI: 10.5863/1551-6776-19.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant and Fosaprepitant Use in Children and Adolescents at an Academic Medical Center

Abstract: OBJECTIVE: To describe the use of aprepitant and fosaprepitant, a neurokinin 1 (NK-1) receptor inhibitor, in children and adolescents at a large academic medical center, for the prevention and management of chemotherapy-induced nausea and vomiting (CINV). METHODS: A retrospective chart review was conducted using an electronic medical record system to evaluate the use of aprepitant and fosaprepitant in all pediatric patients that were discharged from a single academic medical center between Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…The study found fosaprepitant to be safe . Another retrospective study of seven patients who received fosaprepitant prophylaxis for prevention of CINV did not report any adverse events …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The study found fosaprepitant to be safe . Another retrospective study of seven patients who received fosaprepitant prophylaxis for prevention of CINV did not report any adverse events …”
Section: Discussionmentioning
confidence: 85%
“…23 Another retrospective study of seven patients who received fosaprepitant prophylaxis for prevention of CINV did not report any adverse events. 24 RCTs have shown that the addition of aprepitant to ondansetron with or without dexamethasone improved CR rates in children receiving MEC or HEC. 12,20 Bakhshi et al reported significant improvement in CR rates with the addition of aprepitant during the acute phase (48% vs 12 %, P < 0.001).…”
Section: Ta B L E 4 Adverse Events Reported In Study Patientsmentioning
confidence: 99%
“…[30][31][32][33][34][35] Published experience with fosaprepitant in children is limited. [36] This recommendation places a high value on improved CINV control when control is likely to be difficult to achieve and on the negative consequences of uncontrolled CINV. It is a weak recommendation since direct evidence of the efficacy of aprepitant in this context is lacking.…”
Section: Switching From Ondansetron To Granisetronmentioning
confidence: 99%
“…The development of new or optimization of existing antiemetic prophylaxis strategies is therefore urgently needed to improve these patients' quality of life and their treatment outcome. Although the newly available NK 1 -receptor antagonist fosaprepitant has shown a favorable antiemetic efficacy in children undergoing moderately or highly emetogenic chemotherapy (Radhakrishnan et al 2018;Saito et al 2019;Shillingburg and Biondo 2014;Timaeus et al 2018), its use for pediatric patients is not yet proposed by international guidelines (Dupuis et al 2013(Dupuis et al , 2017. Study data on fosaprepitant in children undergoing HSCT are currently not available.…”
Section: Discussionmentioning
confidence: 99%